Rasio Otot-Tulang Ekstremitas Posterior Ayam Pedaging Setelah Pemberian Teh Kombucha Dalam Air Minum - Kumala, Amelia Setya Nur; Djaelani, Muhammad Anwar; Yuniwarti, Enny Yusuf Wachidah (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2017)
Kombucha tea beverage obtained by fermenting sweetened green tea for 12 days with Acetobacter xylinum and Saccharomyces which produce various kinds of organic acids, vitamins, and acts as a probiotic. Kombucha tea role as growth promoter is to enhance the metabolic processes in the digestive system of broiler, so that the nutrients can be absorbed and fulfilled properly for optimal growth and development. The research was conducted from September to October 2014 in the Laboratory of Biological Structure and Function, Diponegoro University. Posterior limb (femur-tibiotarsus) meat-bone ratio analysis was used to investigate the effects of kombucha tea on the productivity of broiler chicken. A total of 20 broiler chickens were randomly divided into 4 treatment concentrations ( 0%, 10%, 20%, and 40% of kombucha tea in drinking water) for 32 days. Statistical analysis using ANOVA at 0,05 significance level and Duncanâ€™s Multiple Range Test showed significantly different results on body weight and water intake, while feed intake, meat weight, bone weight and meat-bone ratio showed no significant results. It can be concluded from this study that the decrease of broiler chicken body weight due to consumption of 40% kombucha tea concentration in drinking water, do not cause a decrease in posterior limb meat and bone weight so that the posterior limb meat-bone ratio were not significantly different.Â Key words: Kombucha tea, broiler chicken, posterior limb, meat-bone ratio.